Assessing the long-term asymmetric relationship between energy consumption and CO2 emissions: Evidence from the Visegrad Group countries - Suproń, Błażej (Economics and Business Review, 2024)
This study investigates the impact of renewable (REW) and non-renewable (NREW) energy usage, along with economic growth, on carbon dioxide emissions in the Visegrad countries, which rely heavily on traditional energy sources. Using data from 1991 to 2021, the analysis employs a panel asymmetric regression with Driscoll-Kraay and FGLS standard errors. The latent cointegration test reveals long-term relationships with asymmetry among the variables. Real GDP fluctuations exhibit a negative impact on CO2emissions for both positive and negative shocks. A reduction in conventional energy source consumption leads to a greater CO2 emission reduction, confirming asymmetry. Conversely, an increase in consumption positively impacts CO2 reduction. However, non-conventional energy sources show no asymmetries. The OLS-based model proposed by Driscoll-Kraay showed reduced standard errors, but lower significance in the estimated parameters compared to the FGLS model. The findings recommend a sustainable energy transition for Visegrad countries by eliminating traditional sources and promoting renewable resources.